2022
DOI: 10.1177/23259671221076048
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes After Arthroscopic Inlay Bristow Surgery With Screw Versus Suture Button Fixation: A Comparative Study of 117 Patients With 3.3-Year Follow-up

Abstract: Background: Some studies have advocated the use of suture button fixation during Bristow-Latarjet surgery to reduce complications associated with screw fixation. However, data comparing these fixation methods are relatively incomplete. Purpose: To investigate the efficacy of modified arthroscopic Bristow-Latarjet surgery and compare the clinical and radiographic outcomes using screw versus suture button fixation. Study Design: Cohort study; Level of evidence, 3. Methods: We evaluated 136 patients with traumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Third, we included two different fixation techniques (screw and button) in the same analysis and there was no subgroup analysis regarding this factor. However, previous studies have shown that fixation methods are not associated with RTS [26]. Finally, another limitation was that the proposed classification of RTS is still not validated in other studies.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Third, we included two different fixation techniques (screw and button) in the same analysis and there was no subgroup analysis regarding this factor. However, previous studies have shown that fixation methods are not associated with RTS [26]. Finally, another limitation was that the proposed classification of RTS is still not validated in other studies.…”
Section: Discussionmentioning
confidence: 96%
“…The evaluation consisted of the following: the graft placement was evaluated using CT scans obtained immediately following surgery. The bone graft was considered lateral if it went beyond the glenoid rim by more than 2 mm, and it was judged to be medial if it was medial to the rim by more than 2 mm [26]. The α angle was defined as the angle between the axis of the screw (or the bone tunnel, button fixation) and the glenoid rim.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These histological findings may explain the excellent radiological outcomes reported in clinical scenarios, consistent with our study. 15,26,30,37,39,50 However, concerns have been increasingly raised regarding the high rate of hardware-related complications, such as screw protrusion or pullout, risk of neurological injuries, and graft osteolysis. 8,16,50 Secondary to some of these concerns, some novel surgical techniques, which use a nonrigid fixation approach for graft positioning via suture anchors or suture suspensory systems, have been comprehensively described.…”
Section: Discussionmentioning
confidence: 99%